THE CONCEPT OF THE URBAN AREAS RECONSTRUCTION PLANNING ON THE BASIS OF THE SCIENTIFIC AND ENGINEERING SUBSTANTIATION - Prusov, Dmitry (Proceedings of National Aviation University, 2014)
The scientific substantiation concept has been proposed for the urban development and territorialplanning reconstruction principles of the urban area sections with dense building and difficult engineering-geologicalconditions for scientific and technical support of all reconstruction processes and recommendations elaboration for asafe and balanced development of built-up territories and more efficient use of housing estates in the present social andeconomic conditions